(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The study of lithological types and structural analysis of rocks of Zango-Kankara-Angwan Lamido on a scale of 1:50,000, Katsina State, northwestern Nigeria at longitudes 70 15’ E and 70 30’E and latitudes 110 45’N and 120 00’N has been carried out. The area consist predominantly of migmatite, older granites and schist, associated with minor quartzite and gneisses. The methodology adopted for the study was mainly primary data in which extensive field visits were done and outlined structural analysis and field relationships were recorded between successive thermo-tectonic episodes The area underwent three phases of tectonic deformation denoted as D1, D2 and D3, whose ages were shown to be Pan-African. At least two intense phases of ductile deformation were identified in the rocks. The rocks have been strongly foliated (especially the gneisses) with crystals showing strong preferred orientations.